Funkcje postępowań antydumpingowych prawa Unii Europejskiej - Ryglewicz, Paweł (My University, 2015)
1. Chapter I begins with showing the development of the anti-dumping regulations all over the world over the last decades. It describes the mechanism which led to the adoption of anti-dumping rules on an international level and the consequences it had for the UE legal system. 2. Chapter II provides an analysis of the economic basis for the anti-dumping regulations. Two opposite options are confronted. The first one assumes that anti-dumping is the necessary guarantee of the stability in international trade and the second regards it as a protective instrument which has a negative impact. 3. Chapter III first provides a description of the institutional framework of the EU anti-dumping regime. It describes the role of the Commission, the Anti-Dumping Committee, the Council and the European Parliament in anti-dumping proceedings, the Court of Justice and to the Court. 4. Chapter IV is devoted to a detailed analysis of the anti-dumping proceeding as it is led by the EU authorities. It includes a description of the analysis provided by the European Commission. 5. The fifth Chapter looks at the situation of undertakings based in non-market economy countries like China and the consequences of this fact on their rights and obligations in anti-dumping proceedings. 6. Chapter VI deals with the situation of European undertaking injured by the dumping. Additionally this part will cover the issue of circumvention of anti-dumping measures. 7. Chapter VII is dedicated to the analysis of the EU interest i.e. interests of undertakings interested in the result of conducted anti-dumping proceeding.
Wydział Prawa i Administracji
Keywords: antydumping; Unia Europejska; WTO; European Commission